INCORPORATING EXTENSIVE READING INTO THE CURRICULUM OF ENGLISH TEACHER EDUCATION - Sri Lestari (Universitas Lambung Mangkurat, 2022)
It is believed that teachers have a significant role in helping students improve their reading performance. Hence, it is crucial to develop a good reading attitude of student teachers because they will become teachers in the future. The teacher education program should prepare student teachers as role model readers. Therefore, the curriculum needs to ensure that the courses help the student teachers build their reading habits. One recommended way to improve reading performance is through extensive reading. This study employed descriptive qualitative research to know how extensive reading is implemented in the English teacher education curriculum and how student teachers view the extensive reading practice. The data resources were from the syllabus, the reflection journals, and the interviews. The study revealed that an extensive reading program could be introduced by integrating it into an existing EFL reading course. Although the English language proficiency did not improve significantly, the student teachers got their reading interest improved and learned new pedagogical skills from extensive reading sessions. It can be concluded that extensive reading can be incorporated into the existing EFL curriculum. However, for more beneficial implications for EFL student teachers, pure extensive reading is highly recommended